(untitled) (Global Journal of Management and Business Research, 2014)
This study aims to highlight the impact of adopting electronic trading System on performance of the Amman Stock Exchange (ASE) represented in the (value traded) and (market capitalisation) where, for the implementation of that, secondary data were collected from (taken from the monthly statistical bulletins of the Stock Exchange) related to the study variables, where an analysis of the difference between the middle two samples: the first study variables before the introduction of the system, and the other after you have inserted, to find out whether there is a significant difference between the size of the stock exchange in trading before and after the introduction of the electronic trading system, and whether there is a significant difference between the value between the market value of securities listed on the stock exchange before and after the introduction of the system.